2021
DOI: 10.21203/rs.3.rs-358254/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined exercise training-induced improvements in executive functions are related to baseline plasmatic levels of Brain-Derived Neurotrophic Factor (BDNF) in middle-aged adults and older with Type 2 Diabetes Mellitus

Abstract: Background: Type 2 Diabetes Mellitus (T2DM) affects many cognitive functions and aerobic plus resistance exercise training, named combined training (CT), by improving metabolic control may mitigate or reverse the cognitive impairment T2DM-related. Brain-derived neurotrophic factor (BDNF) plays a substantial role in cognitive functions. However, the effects of CT on BDNF levels of T2DM subjects are poorly known.Aim: This study analyzed the effects of 8 weeks of CT on circulating BDNF levels and assessed whether… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…The majority of exercise-based studies report that BDNF levels following acute exercise return to baseline values 15–60 min post-exercise cessation, although two studies found significantly lower BDNF concentrations during rest of 2–3 h when compared to basal BDNF values ( Castellano and White, 2008 ; Yarrow et al, 2010 ). In fact, a recent 9-week exercise study found that higher pre-exercise BDNF levels were indeed found to be a significant factor involved with the exercise-induced improvements related to frontal lobe function, but was independent of the exercise-induced alterations in resting peripheral BDNF levels, implying that exercise is able to induce improvements in frontal lobe function but not in inducing long-term changes in the peripheral BDNF ( da Silveira-Rodrigues et al, 2021 ). Could this rapid return to baseline values indicate re-uptake by the brain to exert BDNF’s neuroplastic effects?…”
Section: Resultsmentioning
confidence: 99%
“…The majority of exercise-based studies report that BDNF levels following acute exercise return to baseline values 15–60 min post-exercise cessation, although two studies found significantly lower BDNF concentrations during rest of 2–3 h when compared to basal BDNF values ( Castellano and White, 2008 ; Yarrow et al, 2010 ). In fact, a recent 9-week exercise study found that higher pre-exercise BDNF levels were indeed found to be a significant factor involved with the exercise-induced improvements related to frontal lobe function, but was independent of the exercise-induced alterations in resting peripheral BDNF levels, implying that exercise is able to induce improvements in frontal lobe function but not in inducing long-term changes in the peripheral BDNF ( da Silveira-Rodrigues et al, 2021 ). Could this rapid return to baseline values indicate re-uptake by the brain to exert BDNF’s neuroplastic effects?…”
Section: Resultsmentioning
confidence: 99%